Efeito dos extratos orgânicos de Annona muricata L. e Annona squamosa L. (Annonaceae) sobre o pulgão Aphis gossypii (Glover, 1887) (Hemiptera:Aphididae) e seletividade ao predador Eriopis connexa (Germar, 1824) (Coleoptera: Coccinellidae) - Santos , Lindinalva dos (Universidade Federal de Alagoas, 2017)
The use of botanical extracts has been reported as an alternative to control insect pests in agricultural crops, but the harmful effects of these natural products on the beneficial insect fauna of agricultural ecosystems have to be assessed. The aim of this study was to evaluate the efficiency of seed extracts of sugar apple (Annona squamosa L.) and soursop (Annona muricata L.) on Aphis gossypii (Glover, 1887) (Hemiptera: Aphididae) and its natural enemy, the ladybug Eriopis connexa (Germar, 1824) (Coleoptera: Coccinellidae). Therefore, bioassays were performed with hexane and ethanol extracts at concentrations of 0.125; 0.25; 0.3; 0.4; 0.5; 1.0; 1.5 and 2.0%, to estimate by Probit analysis their lethal concentrations. For the ladybird, it was tested the action by contact, residual effect and ingestion to evaluate survival, oviposition and viability of the eggs. The CL50 and CL99 estimated for A. gossypii were, respectively, 0.39 and 5.47% for the ethanolic extract of sugar apple (EEP); 0.23 and 1.19% for the ethanolic extract of soursop (EEG); 0.47 and 4.39% for the hexanic extract of sugar apple (EHP); 0.42 and 6.38% for the hexanic extract of soursop (EHG). Considering the action of the extracts by contact, the EEG (0.23%) was considered innocuous, on the other hand, the EHG (0.42%) promoted mortality of 30% of insects and is classified as slightly harmful for 1st instar larvae; for adults, only EEP (5.47%) was classified as slightly harmful and the other treatments were classified as harmless, including for the residual effect. Regarding the selectivity of the extracts, the LC50 of EEG and EHG did not affect the survival rate of the ladybirds. By contrast, the EEP in both tested concentrations (0.39 and 5.47%) reduced the rate of survival to zero in less than 7 days, resembling the chemical treatment with Decis®. All treatments reduced the consumption of Anagasta kuehniella eggs, alternative prey, treated with the extracts, reducing the predation and causing as a consequence, oviposition to a decrease in lower concentrations and no egg laid for higher concentrations, affecting fertility and predator the viability of the eggs. The EEG in the concentration of 0.23% was effective in controlling A. gossypii, and its selective natural enemy E. connexa, not interfering with the survival rate of these. === Fundação de Amparo a Pesquisa do Estado de Alagoas === Coordenação de Aperfeiçoamento de Pessoal de Nível Superior === O uso de extratos botânicos é uma alternativa de controle de insetos-praga em cultivos agrícolas, mas os efeitos desses produtos naturais sobre a entomofauna benéfica dos agroecossistemas são necessários. Com isso, o objetivo deste trabalho foi avaliar a eficiência dos extratos de sementes de pinha Annona squamosa L. e graviola Annona muricata L. sobre o pulgão Aphis gossypii (Glover, 1887) (Hemiptera: Aphididae) e seu inimigo natural, a joaninha Eriopis connexa (Germar, 1824) (Coleoptera: Coccinellidae). Para isso, foram realizados bioensaios com os extratos hexânico e etanólico nas concentrações: 0,125; 0,25; 0,3; 0,4; 0,5; 1,0; 1,5 e 2,0%, visando estimar por análise de Probit as concentrações letais. Para a joaninha, foi testada a ação por contato, efeito residual e ingestão para avaliação da sobrevivência, oviposição e viabilidade dos ovos. As CL50 e CL99 estimadas para A. gossypii foram respectivamente, 0,39 e 5,47% para extrato etanólico de pinha (EEP); 0,23 e 1,19% para extrato etanólico de graviola (EEG); 0,47 e 4,39% para extrato hexânico de pinha (EHP); 0,42 e 6,38% para extrato hexânico de graviola (EHG). Na ação dos extratos por contato, o EEG a 0,23% foi considerado inócuo, por outro lado, o EHG a 0,42% promoveu mortalidade de 30% dos insetos, sendo classificado como levemente nocivo para larvas de 1o instar; para adultos apenas o EEP (5,47%), foi classificado como levemente nocivo e os demais tratamentos foram classificados como inócuos, inclusive para o efeito residual. Quanto à seletividade dos extratos às joaninhas por ingestão, as CL50 do EEG e EHG não interferiram na taxa de sobrevivência dos predadores, por outro lado, o EEP nas duas concentrações testadas (0,39 e 5,47%) reduziram a zero a taxa de sobrevivência dos insetos em menos de 7 dias, se assemelhando ao tratamento químico Decis®. Todos os tratamentos reduziram o consumo de ovos de Anagasta kuehniella, presa alternativa, tratados com os extratos, diminuindo a capacidade predatória e, causando como consequência, a diminuição na oviposição para as concentrações menores e nenhum ovo posto para as maiores concentrações, afetando a fecundidade do predador e a viabilidade dos ovos. O EEG na concentração de 0,23% foi eficiente no controle de A. gossypii, e seletivo ao inimigo natural E. connexa, não interferindo na taxa de sobrevivência destes.